Basic applied bioinformatics - Mukhopadhyay, Chandra Sekhar (John Wiley & Sons, 2018)
"This book provides practical guidance in bioinformatics and helps students to optimize parameters for data analysis and then to draw accurate conclusions from the results. In addition to parameter optimization, the text will also familiarize students with relevant terminology"--